Overview Potential Applications of Cold Spray Process for Aviation Industry in Malaysia - O., Nooririnah; Abdullah, Rohana; A.Y, Khalil; M.S, Aludin (scientific.net, 2013)
Abstract. Malaysia plans to become a regional hub for aircraft maintenance and repairs. The country was currently ranked fifth in Asia and tenth in the world in terms of aircraft maintenance,repair and overhaul.It show a positive sign for aviation industry in Malaysia.Maintenance or repair technique play a major role in increasing useful life of the aerospace part and it increase the confident level of the user. This paper is an outcome to discuss Cold spray process as potential repair technique which is widely acclaimed for its ability to perfom a bonding with the underlying material without the creation of heat affected zones which are typical of other deposition processes (thermal spray) and are undesirable in many structural applications. One of potential application for Cold spray process is dimensional restoration or tooling repair like chipped area, if the defect exceed repairable limit that provided by OEM, that part considered scrap. Cold spray can provided environmental friendly solution to thick deposit for dimensional restoration or tooling repair without creation heat affected zone.There is no application yet of this repair technology in Malaysia and on top of that,re-use of material will contribute to cost saving and in-haze the environmet.